EMPOWERING WOMEN AND FOSTERING GREEN ENTREPRENEURSHIP THROUGH HERBAL PRODUCT DEVELOPMENT IN CATUR KINTAMANI - Ni Made Diana Erfiani; Putu Chris Susanto; I Putu Darmawijaya; Putu Indah Lestari (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
This paper explores the emerging herbal tourism in Catur village, Kintamani Bali. It chronicles the development of women empowerment program through the cultivation of herbal medicinal plants in a demonstration plot by Universitas Dhyana Pura and in the family medicinal gardens program (TOGA) of the women farmers’ association (KWT) members, followed by the production, packaging, and marketing of herbal products in the form of healing oil, face oil, hair oil, massage oil, scrubs, and herbal beverages. The article follows the four-year empowerment project, beginning in 2016, which since the initiation of Catur as a tourism village (desa wisata) in 2018 has become one of the unique selling propositions of this rural tourism destination. Since 2018, the project has expanded to cover the village-wide Women for Family Prosperity Assembly (PKK), fostering green entrepreneurship movement among the women within the Catur village community—both related and unrelated to the herbal project. Using the logical framework in analyzing the steps in the women empowerment efforts through herbal plants and products, eventually supporting herbal tourism, this paper discusses the gap between the problems faced by the women in the community and the long-term desired state, then describes the activities taken followed by the outputs produced and the outcomes achieved from the project, and notes some apparent impacts that have occurred in the community since the inception of the project.Keywords: community development, empowerment, green entrepreneurship, herbal products, women